Negara dan Polarisasi Politik: Pelajaran dari Pemilihan Umum 1999 - Ardiantoro, Juri (Laboratorium Sosiologi, Program Studi Sosiologi, Fakultas Ilmu Sosial, Universitas Nahdlatul Ulama Indonesia (UNUSIA) Jakarta, 2022)
This paper attempts to describe and analyze the context of Indonesia’s political changes, particularly in the 1999 elections and those involving state elements and other political actors and structures in the administration of elections in the transitional era. This paper covers four main issues, firstly the 1999 election in the context of Indonesia’s political transition, secondly the institutions for organizing elections in Indonesia, particularly the 1999 General Elections Commission, thirdly the functioning of state elements in the institutional structure and performance of the 1999 General Elections Commission, and finally the democratic political role of the 1999 KPU. In laying a solid foundation for the reform of political institutions in Indonesia. This paper uses a qualitative approach based on the constructivism paradigm. This paper conluded that political change always generates polarization of political forces, both at the state level and at the grassroots level.